SCRIPTED ROLE PLAY-BASED TEACHING TO IMPROVE SPEAKING SKILL OF THE ELEVENTH GRADE STUDENTS OF SMAN 14 PALEMBANG - Jaya Nur Iman (Global Expert: Jurnal Bahasa dan Sastra, 2014)
Role play is very prominent in English speaking classroom because it allows the students to have more oral practice in different social contexts and roles. The purpose of this paper was to find out whether or not scripted role play could make a difference in improving students’ speaking skill achievement. The population of this research paper was all the eleventh grade students of SMAN 14 Palembang in the academic year of 2009-2010. The students were given intervention for 16 meetings including pre-test and post-test in the form of speaking test. The SOLOM rubric was used to measure students’ speaking skill. The findings showed that (1) there was a significant improvement in speaking skill where t obtained of speaking skill was 4.971 (p<0.000), (2) there was also a significant mean difference between the speaking skill of the experimental and control groups where t obtained was 6.804 (p<0.000). Hence, from the research findings, it could be concluded that scripted role play could significantly improve the students’ speaking skill achievement in English teaching and learning environment.